THE INFLUENCE OF ENTREPRENEURIAL COMPETENCE, MARKET ORIENTATION, AND GOVERNMENT SUPPORT ON THE PERFORMANCE OF MSMES IN THE CULINARY SECTOR IN TANJUNG PINANG CITY WITH SELF-EFFICACY AS AN INTERVENING AGENT - M. Faizal Rangkuti; Nolla Puspita Dewi; Ramli (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a significant contribution to the Indonesian economy, including in Tanjung Pinang City, which has great potential in the culinary sector. However, MSMEs in this region still face challenges such as low entrepreneurial competency, weak market orientation, suboptimal government support, and varying levels of self-efficacy. This study aims to analyze the influence of entrepreneurial competency, market orientation, and government support on the performance of MSMEs in the culinary sector in Tanjung Pinang City, with self-efficacy as an intervening variable. The research approach uses a quantitative method with an explanatory design. The research sample consisted of 291 respondents selected using a purposive sampling technique, and data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results show that entrepreneurial competency, market orientation, and government support have a positive and significant effect on MSME performance, both directly and through self-efficacy as a mediating variable. Self-efficacy is proven to strengthen the relationship between internal and external factors on business performance. These findings underscore the importance of enhancing entrepreneurial capacity, consistently implementing market orientation, and optimizing government support in boosting the performance of MSMEs in the culinary sector. This research provides practical implications for local governments and MSMEs in designing integrated business development strategies, as well as theoretical contributions in expanding the study of the relationship between entrepreneurial competency, market orientation, government support, and self-efficacy in the context of MSMEs in Indonesia.